Organizational identity and attitudes towards corruption in Peruvian social sciences university students - Orellana Méndez, Gaspar (2023)
The purpose was to demonstrate the relationship between organizational identity and attitudes towards corruption and also characterize these variables according to socio-demographic criteria. The Organizational Identity Scale (Orellana, et al. 2014) and the Attitudes Towards Corruption Scale (Orellana and Bossio, 2019) were applied to a stratified random sample of 210 students from different social science study programs at a Peruvian public university. It was found that attitudes towards corruption are significantly related to organizational identity (r = .376**) as well as between its dimensions, except between personal identity-attitude towards influence peddling, corporate identity-attitude towards collusion. and Corporate Identity-attitude towards non-compliance with standards. In short, the greater the organizational identity, the greater the attitudes against corruption. Organizational identity must be improved in social sciences university students in order to have better attitudes against corruption, as well as carrying out new research in populations of other ages and social sectors, in addition to corroborating the relationship of implication of these variables.